Penilaian Kualitas Permukaan Jalan dengan Penggunaan Pavement Condition Index (PCI) di Jalan Adiwerna II, Kabupaten Tegal - Marwanto, Riza Phahlevi; Azel Rizal Jovian; Hadi, Suprapto (JURAL RISET RUMPUN ILMU TEKNIK, 2024)
This study evaluates the pavement condition of 3,300 meters of Adiwerna Highway II using the Pavement Condition Index (PCI) method based on the ASTM D6433-18 standard. The road is divided into 18 segments to facilitate analysis, with data obtained through visual surveys. The results show five main types of damage, dominated by patches (84%). PCI values ​​range from 38–86 with an average of 69 ("Fair" category), indicating the need for planned maintenance. The most critical segment is at STA 3+100–3+200 (PCI 38). The study recommends a more economically efficient preventive maintenance strategy, and suggests specific treatments according to the type of damage. This study supports the development of data-driven road asset management for infrastructure maintenance optimization.